THE USE OF VIDEO IN TEACHING SPEAKING - HILMANSYAH, Iman (2013)
The research entitled "The Use of Video in Teaching Speaking" is aimed to answer the question whether or not the use of video significantly improves the students' speaking ability. Furthermore the students' responses to the use of video as a media in learning speaking are also investigated. This research involved two classes consisted of experimental group which was taught by using video and control group which was taught by using audio tape. The data were analyzed by using quantitative method by comparing the mean scores of both group in pretest and posttest. Moreover, this research involved questionnaires to find out the students' responses in learning speaking through video. The result showed that the use of video improved students' speaking ability. It was evidenced by the result of statistical computation (independent t-test) which revealed that the value of tobt(13.377) was greater than tcrit(2.064, α=0.05, df= 24). In conclusion, the null hypothesis was rejected. Meanwhile, the result of the questionnaire showed that most of students agreed that learning speaking through video can encourage their motivation and improve their speaking ability.Penelitian yang berjudul "Penggunaan Video Dalam Mengajarkan Berbicara" bertujuan untuk menjawab pertanyaan tentang mampukah penggunaan video meningkatkan kemampuan berbicara siswa secara ssignifikan. Lebih jauhnya untuk mengetahui respon siswa terhadap penggunaan video sebagai media untuk belajar berbicara. Penelitian ini menyertakan dua kelas yang terdiri dari kelas eksperimen yang belajar dengan menggunakan video dan kelas control yang belajar dengan menggunakan audio tape. Data dianalisa dengan menggunakan metode kuantitatif dengan membandingkan nilai mean dari kedua kelas baik itu pretest maupun posttest. Selain itu, penelitian ini menggunakan kuesioner untuk mengetahui respon siswa dalam belajar berbicara menggunakan video. Hasil dari penelitian ini menunjukan bahwa penggunaan video mampu meningkatkan kemampuan berbicara siswa. Ini dibuktikan dengan penghitungan hasil statistic (independen t-test) yang meunjukkan data sebagai berikut tobt(13.377) yang mana lebih besar dari tcrit(2.064, α=0.05, df= 24). Null hypothesis nya ditolak, selain itu hasil dari kuesioner menunjukkaan bahwa kebanyakan dari siswa setuju bahwa belajar berbicara melalui video dapat meningikatkan motovasi siswa dan meningkatkan kemampuan berbicara siswa.